2019
DOI: 10.1136/bmjdrc-2017-000497
|View full text |Cite
|
Sign up to set email alerts
|

Experiences and challenges of adults living with type 2 diabetes mellitus presenting at the University Teaching Hospital in Lusaka, Zambia

Abstract: ObjectiveThe study explored the experiences and challenges of adults living with type 2 diabetes mellitus (T2DM) presenting at the University Teaching Hospital (UTH) in Lusaka.Research designA qualitative descriptive study was conducted. The research relied on purposive sampling to select 28 participants for in-depth interviews. Participants were interviewed during clinical visits at UTH.ResultsViews from participants showed that some adults living with T2DM experienced physical and mental illnesses. Participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 22 publications
0
5
1
3
Order By: Relevance
“…The presence of autonomic neuropathy, particularly the cardiac manifestation, has been correlated with an elevated mortality rate [ 61 ]. In our study, 69.6% of the male patients with DPN reported erectile dysfunction versus 50% in the study by Mwila et al in Zambia [ 48 ]. A Nigerian study reported known inadequacies in the treatment of DPN in Africa [ 61 ].…”
Section: Discussioncontrasting
confidence: 67%
See 3 more Smart Citations
“…The presence of autonomic neuropathy, particularly the cardiac manifestation, has been correlated with an elevated mortality rate [ 61 ]. In our study, 69.6% of the male patients with DPN reported erectile dysfunction versus 50% in the study by Mwila et al in Zambia [ 48 ]. A Nigerian study reported known inadequacies in the treatment of DPN in Africa [ 61 ].…”
Section: Discussioncontrasting
confidence: 67%
“…The low socio-economic level of patients with diabetes has been widely reported in the African medical literature [ 47 , 48 ]. Most patients in our study had a low socio-economic status.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As diretrizes de tratamento para pessoas com diabetes incluem ações complexas e específicas e, as pessoas que vivem com a doença têm dificuldades em autogerenciar a sua condição de saúde para alcançar o controle da glicemia (SOCIEDADE BRASILEIRA DE DIABETES, 2020; BLASCO-BLASCO; PULG-GARCIA; PIAY et al, 2020). Estudo descreve que os pacientes com diabetes mellitus 2 consideram difícil a realização do tratamento, principalmente em relação a alimentação, prática de exercícios físicos e uso de medicação (MWILA;BWEMBYA;JACOBS, 2019).…”
Section: Introductionunclassified